Some properties of q- close-to-convex functions - Uçar, H. Esra Ozkan; Mert, Oya (Hacettepe Univ, Fac Sci, Hacettepe Univ, Fac Sci, Beytepe, Ankara 06800, Turkey, 2017)
Quantum calculus had been used first time by M.E.H.Ismail, E.Merkes and D.Steyr in the theory of univalent functions [5]. In this present paper we examine the subclass of univalent functions which is defined by quantum calculus.
Keywords: q- convex function; q- close to convex function; growth theorem; distortion theorem; coefficient inequality